Cancer Vaccines in the World of Immune Suppressive Monocytes (CD14+HLA-DRlo/neg Cells): The Gateway to Improved Responses - Laborde, Rebecca R.; Lin, Yi; Gustafson, Michael; Bulur, Peggy; Dietz, Allan B. (Frontiers in Immunology, 2014)
Dendritic cells are an important target in cancer immunotherapy based on their critical role in antigen presentation and response to tumor development. The capacity of dendritic cells to stimulate anti-tumor immunity have led investigators to use these cells to mediate anti-tumor responses in a number of clinical trials. However, these trials have had mixed results. The typical method for generation of ex-vivo dendritic cells starts with the purification of CD14+ cells. Our studies identified a deficiency in the ability to generate mDC using CD14+ cells from cancer patients that corresponded with an increased population of monocytes with altered surface marker expression (CD14+HLA-DRlo/neg). Further studies identified systemic immune suppression and increased concentrations of CD14+HLA-DRlo/neg monocytes capable of inhibiting T cell proliferation and DC maturation. Together these findings strongly suggest that protocols aimed at immune stimulation via monocytes/dendritic cells, if optimized on normal monocytes or in systems without these suppressive monocytes, are unlikely to engender effective DC maturation in vitro or efficiently trigger DC maturation in vivo. This highlights the importance of developing optimal protocols for stimulating DCs in the context of significantly altered monocyte phenotypes in patients.